Study on the Relevance of Robotics Technology - М. V. Yadrovskaya; I. V. Gurin (Advanced Engineering Research, 2023)
Introduction. Robotic technologies serve as an important indicator of the technological and economic state of the country, they also affect the lives of individuals. Their development is a promising and urgent task affecting many aspects of the life of modern society. Currently, robotics is going through another stage of development, which has its own characteristics, new directions.   The work aims at analyzing the situation and ways of development of this industry in the world and in our country, as well as the attitude of people to the use of robotic systems and their willingness to improve them.   The topic under consideration is understudied.   Materials and Methods. In the presented work, the historical aspects of the formation of unique robotic technologies are defined, the ratio of the number of manufacturers and consumers of robotic products in the world is specified, the areas of the robotic technology application are named. The central place in the research is given to the results of an online survey conducted by the authors. Its statistical analysis made it possible to study, using specific data, the factors that influence the spread of robotic systems and robotic technologies and contribute to them.   Results. The survey results, on the one hand, showed a high assessment of the prospects of robotic systems given by the respondents, and confirmed that young people have an interest in robot-making technologies. On the other hand, they allowed us to note the high level of knowledge in the field of robotic technologies among engineering students and the presence of more than elementary knowledge of these technologies among representatives of other special fields. In the opinion of the authors, there are all prerequisites for the further successful development of these technologies.   Discussion and Conclusions. The analysis of the use of robotics in the world and in our country, as well as the results of the survey conducted by the authors, enable to conclude that these technologies are developing and will continue to develop actively, and the interest of current students in this, confirmed by the answers to the questionnaire, will contribute to the wider introduction of robots into the lives of future generations.